2018
DOI: 10.1080/20013078.2018.1494482
|View full text |Cite
|
Sign up to set email alerts
|

A new assay to evaluate microvesicle plasmin generation capacity: validation in disease with fibrinolysis imbalance

Abstract: Among extracellular vesicles, leukocyte-derived microvesicles (LMVs) have emerged as complex vesicular structures. Primarily identified as procoagulant entities, they were more recently ascribed to plasmin generation capacity (MV-PGC). The objectives of this work were (1) to develop a new hybrid bio-assay combining the specific isolation of LMVs and measurement of their PGC, and compare its performance to the original method based on centrifugation, (2) to validate MV-PGC in septic shock, combining increased l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
2
17
1
1
Order By: Relevance
“…When comparing each marker between the different study groups, no statistically significant differences were found, except in the CD45, leukocyte common antigen, where the Mvs of patients (remission, local and metastasis, respectively) have 1.9, 1.8 and 2.8 times higher intensity of fluorescence com-pared to the healthy women group. These data are in agreement with previously reported data indicating that both leukocytes and Mvs from leukocytes have the capacity to generate plasmin (Lacroix et al 2007(Lacroix et al , 2012Chaari et al 2014;Cointe et al 2018).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…When comparing each marker between the different study groups, no statistically significant differences were found, except in the CD45, leukocyte common antigen, where the Mvs of patients (remission, local and metastasis, respectively) have 1.9, 1.8 and 2.8 times higher intensity of fluorescence com-pared to the healthy women group. These data are in agreement with previously reported data indicating that both leukocytes and Mvs from leukocytes have the capacity to generate plasmin (Lacroix et al 2007(Lacroix et al , 2012Chaari et al 2014;Cointe et al 2018).…”
Section: Resultssupporting
confidence: 94%
“…Altogether, our data suggest that circulating Mvs may be involved in plasmin generation in vivo and play thereby a key role in fibrinolysis and pericellular proteolysis. Direct detection and quantification of Mvs fibrinolytic activity in circulating blood could be of potential diagnostic and prognostic value in patients with metastatic breast cancer (Angelucci et al 2000;Cointe et al 2018). Future studies should investigate the impact of blocking fibrinolytic activity in breast cancer patients as a potential treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocapture on magnetic beads may represent a useful alternative. 108 The two main approaches which have been applied to evaluate the potential of MVs biomarker of cancer associated thrombosis are: (1) the antigenic detection of procoagulant molecules at the surface of MVs 111 or (2) the functional capacity of MVs to generate factor Xa, thrombin, or a clot. Combined strategies have also been developed 112 (►Table 2).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In a preliminary study, we showed that the MVs fibrinolytic activity was significantly higher in septic shock patients who survived compared to those who died and that this MV-dependent activity was inversely correlated with multiorgan failure scores and ischemic markers. 108 However, to what extent the fibrinolytic side may counterbalance the procoagulant side and play a significant role in the cancerassociated thrombosis pathophysiology is still largely unknown. Similarly, whether the coagulofibrinolytic balance of MVs is a better predictor of the occurrence of thrombosis in cancer patients rather their procoagulant activity alone, remains to be evaluated with suitable methodologies.…”
Section: A More Complex Role Of Microvesicles In Hemostasismentioning
confidence: 99%
“…The plasmin generation capacity of the EVs was assessed by isolating EVs and measuring their ability to initiate plasmin generation using a chromogenic assay [10,11]. In brief, 200 µL citrate-anticoagulated plasma was diluted (1:2) in PBS/ BSA (phosphate buffer saline, 0.1% bovine serum albumin and 0.1% NaN 3 ) and incubated for 1 h at room temperature under mild rotation with magnetic beads (M450 Dynabeads; InVitrogen/Dynal, Oslo, Norway) coated with specific antibodies (anti-CD15).…”
Section: Fibrinolysismentioning
confidence: 99%